(untitled) (Proceedings of the International Conference on Future of Education, 2025)
Abstract: The development of digital technology has transformed how firms work, resulting in a dramatic shift in the skills and knowledge required for success in today’s business climate. Consequently, business education has had to adapt to these developments to remain relevant. In Nigeria, the conventional face-to-face method of learning has been the predominant mode of instruction in business education. However, as digital technology has been more widely used, online learning has become an appealing option. The impact of digital transformation on business education has been a highly debated topic in recent times, particularly in developing countries like Nigeria. Thus, this study aims to compare the traditional and online learning approaches in order to understand the effects of digital transformation on business education in Nigeria. A sample of 351 online and traditional learning environment students was surveyed using purposive sampling. The study used structural equation modeling (SEM) and multi-group analysis (MGA) for data analysis. The result shows that the direct relationship analysis revealed a significant positive impact of digital transformation on business education indicating that the adoption of digital technologies significantly enhances educational outcomes. Furthermore, the MGA results, which compared path coefficients between online and traditional groups, showed a small difference suggesting a consistent impact of digital transformation across both learning modalities. These findings show the importance of integrating digital transformation strategies in educational institutions to improve the quality of business education universally, regardless of the learning environment. This study provides valuable insights for educational policymakers and administrators, advocating for continued investment in digital technologies to foster improved educational experiences and outcomes.